The Muslim Emigration in Western Anatolia - Elçin Macar (Cahiers Balkaniques)
With the Balkan Wars, the whole region was introduced to a new concept: Ethnic cleansing. States looking to homogenize their population did this in two ways: either by treaty or by force. Population statistics thus became one political instrument and then started the “ethnic engineering”. Among Anatolian Christians, Ottoman Greeks were the first target of the CUP who feared losing the “last remaining territory”. Talat Pasha, Minister of the Interior, talked to German diplomats about ridding the country of “internal enemies”. After expulsions, terrorism and deportations between 1913 and 1918, on both sides of the Aegean, almost half the population of 17.5 million changed places. The era’s worst legacy is the idea that states have a right to exchange or deport their populations like property.